Case Report: Unusual Presentation of Myositis Ossificans of the Elbow in a Child Who Underwent Excessive Postoperative Rehabilitation Exercise - Cao, Jin; Zheng, Hua Jiang; Sun, Jing Hua; Zhu, Huan Ye; Gao, Chao (Frontiers in Pediatrics, 2021)
Traumatic myositis ossificans (MO) is an unusual complication after muscle injury which predominantly seen in young adults and adolescents. Pediatric MO cases are even rarer. We report an 8-year-old girl who was diagnosed with a lateral humeral condyle fracture. She was treated surgically, and her elbow joint was fixed with plaster. Rehabilitation exercise was administered one month after the operation. Due to the wrong exercise method, a palpable bony mass appeared around the elbow 1 month later. The clinical radiological diagnosis showed MO, and conservative treatment was administered. After 3 years of follow-up, the affected limb functioned well, with no sign of recurrence. We report this long-term follow-up case of MO resulting from excessive rehabilitation exercise.